(untitled) (Bangladesh Journal of Urology, 2020)
Objective: To evaluate the association of detrusor muscular activity with outcome of TURP in patients with severity of bladder outflow obstruction. Methods: This is a hospital based cross sectional study conducted in the Department of Urology of Dhaka Medical College Hospital, Dhaka.Elderly male patients having lower urinary tract symptoms (IPSS=20-35) with no retention (non-catheterized patient), who attended in Dhaka Medical College Hospital, were included in the study. A total of 73 patients meeting the enrollment criteria were included in the study. They were evaluated by history, physical examination including DRE and necessary investigations to identify the potential candidates for TURP. Then the potential participants were counseled for Urodynamic study. All patients underwent TURP by expert surgeon. Three months after TURP, repeat Urodynamic study was done and the results were compared to see the outcome. Afterward the data were plotted for the clarification of detrusor contractility at three levels: normal detrusor contractility (voiding pressure 40-60cm of water), detrusor over activity (voiding pressure >60cm of water) and detrusor under activity (voiding pressure <40 cm of water). According to the provisional ICS nomogram for the analysis of voiding, patients were divided into three classes. In BOO Index(PdetQmax-2Qmax),obstructed(BOOI > 40); equivocal(BOOI=20-40);Unobstructed(BOOId” 20) are taken into consideration. The test statistic used to analyze the data was descriptive statistics and ANOVA test. The level of significance was set at 0.05 and P<O.05 was considered significant. Results: Out of 73 patients 8 didn’t attend follow up session and hence excluded keeping 65 for final analysis. The mean age was 66.3 ± 9.7 years (50- 87 years) .Detrusor over activity was present in 13(20%), normal detrusor contractility was observed in 46(70.8%) and weak contractility in 6(9.2%). Peak urinary flow rate was almost similar among patients of different groups. However, voided volume and residual volume were lowest in overactive group and highest in underactive group, while normal group was in between two (p = 0.007 and p = 0.046 respectively). Maximum urinary flow rate and voided urine between patients of moderate and severe bladder outlet obstruction were almost comparable (p =0.120 and p = 0.270 respectively). However, residual urine volume was much higher in the patients of moderate BOO than that in severe BOO (p = 0.001).The patients of OAB experienced a significant improvement in percentage of reduction of residual urine volume compared to normal and underactive bladder (p = 0.002), However, there were no significant difference among the patients with overactive, normal and underactive bladder with respect to peak urinary flow rate and voided urine volume (p = 0.499 and p = 0.847 respectively). Conclusion: TURP is an effective surgical procedure for treatment of BPH, especially for patients with severe degree of BOO with normal or overactive detrusor contraction. Bangladesh Journal of Urology, Vol. 18, No. 2, July 2015 p.56-61